Adult Children Migration and Perceived Mental Health of Elderly Parents in Rural Area of Parbat - Sharma, Anju Kumari; Tamrakar, Neeta; Karmacharya, Ranjita (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Increasing trend of elderly population across the world along with the increased rate of adult children migration has brought in significant impact on mental health of elderly population which has been a major concern nowadays. This study aimed to assess relationship of adult children migration and perceived mental health of elderly parents in the rural area of Parbat. Methods: A descriptive cross- sectional study was conducted among 190 elderly parents of Modi rural municipality of Parbat district. A structured interview with validated Nepali version of DASS-21 (Depression, Anxiety, and Stress Scale) was used to assess the perceived mental health of elderly parents. Results: Study findings showed that 57.9% respondents had at least one migrant child. Depression, anxiety and stress were prevalent among 15.8%, 28.9% and 13.2% respondents respectively. Perceived mental health of the respondents was significantly associated with age, gender, educational status, marital status, living arrangement and use of internet services (p<0.05). Stress among respondents was associated (p=0.016) with migration of adult children. Conclusions: Mental health problems are prevalent among elderly parents and children migration is the significant influencing factor for mental health among them.